BRAIN HEALTH MONITORING PLATFORM: THE CLINICAL APPLICATIONS OF DIGITAL TECHNOLOGY IN NEUROLOGICAL DISORDERS. (11th November 2018) - Ritchie, M M; Au, R; Alosco, M L; Mez, J; Kohli, M; Lin, H; Pfeifer, N; Comeau, D
Abstract: There is growing evidence that smart and wearable technologies can be used to study the role of key lifestyle factors in the development and clinical manifestation of neurological disorders. It is now possible to build a brain-health monitoring platform that can track disease progression remotely in the person's natural environment. However, the utility and feasibility of applications and wearables has yet to be investigated on a large-scale basis. This study examines the effectiveness of using digital-health metrics as an adjunctive evaluation/monitoring system for brain-health with two functions: (1)to screen and validate technologies used to assess and monitor diseases and (2)to gather a continuous flow of participant data. This platform reduces dependence on traditional labor-intensive, and relatively sporadic clinic examinations to low-cost, lower burden assessments. Furthermore, we are developing an infrastructure for scalable data sharing and building an ecosystem of key stakeholders to help navigate the ever changing health IT landscape.